Penerapan Ghinā’ ʿArabī sebagai Kegiatan Penunjang Giat Berbahasa Arab Siswa MTs NU Nurul Huda Semarang - Hidayati Nurul Hanifah (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2022)
This article aims to describe the application of ghinā’ ʿarabī as an activity to support active Arabic language students at MTs NU Nurul Huda Semarang. The use of the ghinā’ method is considered more effective than other methods in supporting active Arabic students, especially for MI and MTs students. The method used in this study is a qualitative descriptive method. The data collection techniques were obtained through observation, interviews, and documentation. The application of ghinā’ ʿarabī to support the habituation of students' active learning at MTs NU Nurul Huda Semarang is very effective. Students become more enthusiastic and easier to understand and learn Arabic. This method also helps teachers in overcoming the lack of student focus in learning. In addition, students and teachers can also carry out teaching and learning activities in a conducive and fun way.